1993
DOI: 10.1097/00006123-199309000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Four Intravenous Anesthetic Agents on Motor Evoked Potentials Elicited by Magnetic Transcranial Stimulation

Abstract: The influence of four intravenous anesthetic agents on motor evoked potentials (MEPs) elicited by transcranial magnetic stimulation (magnetic MEP) was examined in 77 subjects. The patients were anesthetized by a continuous intravenous infusion of one of the following anesthetic agents: propofol, etomidate, methohexital, or thiopental. Comparable anesthetic effects among the four agents were achieved by computing an infusion scheme for each drug. Infusion rates were increased slowly in a step-wise manner in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Several uses require the application of repetitive stimuli, such as MEP monitoring during orthopedic and neurosurgical operations [38]. Single transcranial magnetic stimuli during surgery are not sufficient for eliciting suprathreshold motor responses because anesthetic agents substantially suppress I waves induced by transcranial stimuli [20, 24,33,36,[38][39][40][41]. Therefore repetitive stimulation at high frequencies and intensities is used to obtain temporal summation of descending pyramidal tract volleys at spinal α-motoneurons and to achieve reliable MEP monitoring [18,35].…”
mentioning
confidence: 99%
“…Several uses require the application of repetitive stimuli, such as MEP monitoring during orthopedic and neurosurgical operations [38]. Single transcranial magnetic stimuli during surgery are not sufficient for eliciting suprathreshold motor responses because anesthetic agents substantially suppress I waves induced by transcranial stimuli [20, 24,33,36,[38][39][40][41]. Therefore repetitive stimulation at high frequencies and intensities is used to obtain temporal summation of descending pyramidal tract volleys at spinal α-motoneurons and to achieve reliable MEP monitoring [18,35].…”
mentioning
confidence: 99%
“…Propofol has been shown to be a potent suppressor of MEPs induced by electrical and magnetic stimulation with a single pulse [20,[36][37][38][39]. Kalkman et al [20] reported that sustained reduction of MEP amplitude occurred after a single dose of 2 mg·kg Ϫ1 propofol.…”
Section: Propofolmentioning
confidence: 99%
“…Kalkman et al [20] reported that sustained reduction of MEP amplitude occurred after a single dose of 2 mg·kg Ϫ1 propofol. Taniguchi et al [36] investigated the effects of propofol on MEPs induced by transcranial magnetic stimulation. They documented that the reduction of MEP amplitude was very large and MEPs were completely abolished before adequate anesthesia was achieved.…”
Section: Propofolmentioning
confidence: 99%
“…102 When a stimulus has been transmitted via the synapse, so-called EPSPs are registered in the postsynaptic membrane. 11 The EPSPs indicate the depolarization of the postsynaptic cell, which can last for up to 20 msec.…”
mentioning
confidence: 99%